2022
DOI: 10.1021/acsanm.2c03416
|View full text |Cite
|
Sign up to set email alerts
|

Review of 2D Graphitic Carbon Nitride-Based Membranes: Principles, Syntheses, and Applications

Abstract: Membrane separation is a central area of research in chemical engineering because of its important status as the key technology in chemical separation and water treatment processes. Recently, polymeric graphitic carbon nitride (g-C3N4) has emerged as a candidate material for membrane applications because of its appealing physiochemical properties and ease of fabrication. Herein we review the progress of g-C3N4-based membranes, including the peculiarity of two-dimensional (2D) g-C3N4, the tailoring of functiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 147 publications
0
15
0
Order By: Relevance
“…In comparison to conventional polymeric membranes, strong in-plane noncovalent bonds of the 2D-material-based membranes enhanced the mechanical strength and chemical stability, which are needed for the membrane to be utilized under harsh conditions. 75 As a result, the tensile test ( Fig. 3f and S27 † ) showed that the ultimate strength and Young's modulus of the pCN/CNTs membrane were better than those of the control pCN + CNTs and CNTs membranes, which were filtered using pCN and/or CNTs mixtures without PPA compounding.…”
Section: Resultsmentioning
confidence: 94%
“…In comparison to conventional polymeric membranes, strong in-plane noncovalent bonds of the 2D-material-based membranes enhanced the mechanical strength and chemical stability, which are needed for the membrane to be utilized under harsh conditions. 75 As a result, the tensile test ( Fig. 3f and S27 † ) showed that the ultimate strength and Young's modulus of the pCN/CNTs membrane were better than those of the control pCN + CNTs and CNTs membranes, which were filtered using pCN and/or CNTs mixtures without PPA compounding.…”
Section: Resultsmentioning
confidence: 94%
“…2.5.2.1 Hard templates. Hard templates like porous anodic metal oxide (i.e., alumina oxide (AAO) and ZnO) 82,112,113 and silica (i.e., SBA-15, SBA-16, FDU-12, and KIT-6) [114][115][116] are exhaustively used for the preparation of porous g-C 3 N 4 with different structures (i.e., nanotubes, nanorods, and nanospheres). This followed pioneering work done by Goettmann et al 117 who mixed cyanamide with 12 nm SiO 2 particles in water, which was heated to 550 °C for 2h and then 4 h, followed by immersion in NH 4 HF 2 for two days to remove the silica template.…”
Section: Green Methods For the Synthesis Of G-c 3 N 4 -Based Catalystsmentioning
confidence: 99%
“…24,77–80 There are various reviews discussing in detail the preparation methods of g-C 3 N 4 . 21,28,81–83…”
Section: Graphitic Carbon Nitride Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…For these reasons, g-C 3 N 4 membranes are used as active agents or emulsifiers on colloidal surfaces, and their ability to maintain high surface activity also in liquid-liquids, liquid-gases and liquid-solids has led to their application in cleaning, anti-fouling, gas purification, biological separation and wastewater treatment. 48 The g-C 3 N 4 with structural defects may allow the production of amine groups (primary and/or secondary) on the terminating edge of its monolayer, presenting basicity, which leads to the formation of g-C 3 N 4 multifunctionality. Thus, the surfaces of g-C 3 N 4 materials are endowed with fundamental nucleophilic properties that promote their valuable applications.…”
Section: Properties Of G-c 3 Nmentioning
confidence: 99%